(untitled) (ModaPalavra e-periódico, 2022)
This study was conducted with the main objective of mapping and analyzing how the concept of ergonomics has been used in research in the area of fashion and clothing design in Brazilian magazines, using the scope of six magazines understood as highly relevant to these areas, these being: Modapalavra e-periodic; Dobra[s]; Achiote.com - Revista Eletrônica de Moda; Revista de Ensino em Artes, Moda e Design; Projética; and Educação Gráfica. In methodological terms, this is a descriptive-exploratory research, of a quantitative-qualitative nature, carried out through a systematic analysis of the bibliography. In relation to the main results, 23 papers were analyzed, reaching the central understanding that most of these articles aimed at solving problems related to clothing manufacturing through the development of ergonomic products, highlighting the importance of the fashion designer to understand the concept of ergonomics and apply it effectively in the production chain.